Influence of Neuropeptide Y and Neuropeptide Y 2 Receptor Variants in Acute Coronary Syndrome - Soares,Fábia C. S. (2022)
Abstract Background The neuropeptide Y (NPY) is one of the most abundant neurotransmitters in the nervous system. NPY acts as a potent stimulator of angiogenesis, inflammation, and adipogenesis, through the NPY 2 receptor (NPY2R). Changes in the NPY signaling pathway have been linked to Acute Coronary Syndrome (ACS). Objectives The purpose of this study is to determine the association between variants in the NPY and NPY2R genes, as well as the severity of acute coronary syndrome (ACS). Methods Approximately 221 ACS patients and 278 healthy controls were selected for this study. Four variants in NPY and two variants in NPY2R genes were genotyped using Taqman allelic discrimination and sequencing. The Chi-square and Fisher's exact tests were used to verify the genotype frequencies. The logistic regression analyses were used for the evaluation of the studied variables. Haplotype analysis was used to evaluate the linkage disequilibrium (LD) between the variants (p<0.05). Results An association of NPY c.20T>C variant was found with the ACS group when compared to the healthy group. In the analysis between variants and risk factors in the ACS group, NPY c.84G>A was associated with hypertension. The analysis between TIMI risk showed a significance for NPY c.20T>C between the low and intermediate/high TIMI risk groups. In the haplotype analysis, strong linkage disequilibrium (LD) was found between the variants NPY c.150G>A and NPY c.-485T>C. Conclusion The NPY c.20T>C variant appears to contribute to the development of ACS. The NPY2R c.-1116A>G variant may contribute to the early development of ACS and the NPY c.84G>A variant appears to contribute to the development of hypertension. In addition, the NPY c.20T>C is associated with a protective effect in ACS severity.